2014
DOI: 10.1002/srin.201400031
|View full text |Cite
|
Sign up to set email alerts
|

Study on Desulfurization Abilities of Some Commonly Used Desulfurization Agents

Abstract: The desulfurization abilities of some commonly used agents, namely fluidized CaO, CaC 2 , commercial-CaO, Mg, MgO, CaO Á MgO, and mixtures of commercial-CaO-Mg were studied and compared under the same experimental conditions in a laboratory furnace at 1773 K. The desulfurization mechanisms of CaO Á MgO, commercial-CaO, and mixtures of commercial-CaO and Mg were also studied. While fluidized CaO showed the best performance, commercial-CaO mixed with 20 mass% Mg achieved the second best desulfurization. Mg-granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…EDS analysis indicated the presence of TiO 2 . The result is very similar to silicon in liquid iron [11,12]. However, vanadium is not accumulated on the surface of CaO.…”
Section: Resultssupporting
confidence: 56%
“…EDS analysis indicated the presence of TiO 2 . The result is very similar to silicon in liquid iron [11,12]. However, vanadium is not accumulated on the surface of CaO.…”
Section: Resultssupporting
confidence: 56%
“…These results along with the re‐evaluation of the thermodynamic data reported in the literature leads to an evident conclusion that the use of ZnO to desulfurize hot metal by the formation of ZnS gas is not possible to any extent. The present authors12 have found that ZnO cannot help the slag to increase its desulfurization power. Hence, a conclusion that ZnO cannot be used as desulfurization agent can be drawn.…”
Section: Discussionmentioning
confidence: 52%
“…The first mechanism is that ZnO helps the slag to increase its capacity of capturing sulfur. The second mechanism is the formation of ZnS gaseous species, which is suggested by Kumar et al9–11 A recent study12 has evidently ruled out the first alternative. Hence, the objective of this paper is to perform lab scale hot metal desulfurization experiments using ZnO to study the possibility of desulfurization by the second mechanism, viz.…”
Section: Introductionmentioning
confidence: 93%
“…Among commonly used agents, namely,f luidized CaO, CaC 2 , commercial CaO, Mg, MgO, CaO·MgO, and mixtures of com-mercialC aOÀMg, the best resultsa re shown by commercial CaO mixed with 20 mass %M g. [222] Slow growth of CaS on CaC 2 particles led to poorer resultsf or carbide compared with that of Flucal CaO particles( Figure 52). Nevertheless, the activity was estimated by the amount of an additive, andl arger amounts were possible.…”
Section: Usage Of Calcium Carbide In Alloymakingmentioning
confidence: 99%